High-refractive optical adhesive, preparation method and application thereof
Patent Information
- Application Number
- CN202611139130.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]为了克服现有高折光学胶水存在的折射率失配、偏振适配性差、固化应力大和稳定性不足等问题,本申请提供一种高折光学胶水及其制备方法与应用
1. 本申请通过采用高折环氧丙烯酸酯树脂、含硫甲基丙烯酸酯单体与硅烷偶联剂改性无机填料的协同复配,从而获得了一种兼具高折射率、低收缩率、无偏振干扰和高可靠性的高折光学胶水,其折射率能够精准匹配玻璃基片(1.50~1.55)和光栅树脂层(1.50~1.55),从根本上消除了界面光学损耗与偏振畸变,同时大幅降低了贴合应力导致的光栅形变问题,能够充分满足双片同材质偏振体全息光波导精密贴合封装的严苛要求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of optical adhesive technology, specifically to a high-refractive-index optical adhesive, its preparation method, and its application. Background Technology
[0002] Polarized volume holographic (PVG) waveguides are core optical components of augmented reality near-eye display (AR) devices. Due to their excellent polarization-selective diffraction characteristics and high diffraction efficiency, they have become one of the mainstream optical solutions for lightweight AR devices. Currently, the industry mainly uses two glass substrates to fabricate coupling gratings and coupling gratings respectively, and then uses optical adhesive to bond the two substrates together into an integrated waveguide assembly, thereby achieving polarized beam coupling, total internal reflection transmission, and pupil-expanding imaging functions.
[0003] However, existing bonding adhesives for dual-layer grating waveguide structures have the following drawbacks: First, refractive index mismatch; the refractive index of conventional optical adhesives (1.40~1.45) is lower than that of the glass substrate (1.50~1.55) and the resin layer of the polarizing holographic grating (1.50~1.55), leading to easy scattering, reflection, and refraction of light at the interfaces between the adhesive layer and the substrate, and between the adhesive layer and the grating layer. This damages the polarization diffraction characteristics of the grating, resulting in optical quality problems such as image ghosting, light leakage, and reduced contrast. Second, poor polarization compatibility. Ordinary optical adhesives exhibit polarization anisotropy and low extinction ratio, interfering with the polarization state during polarized light transmission, causing the polarization modulation function of the PVG grating to fail and severely affecting image quality. Third, high curing stress. The shrinkage stress generated during the curing process of traditional adhesives easily induces deformation of the grating microstructure and warping of the glass substrate, leading to beam transmission path deviation, reduced optical accuracy, and even irreversible damage to the grating groove structure. Fourth, insufficient stability. Ordinary existing adhesives have poor aging resistance and temperature cycling resistance, and are prone to yellowing and delamination, which cannot meet the requirements for long-term stable operation of polarizing holographic waveguides.
[0004] Therefore, there is an urgent need to develop a special high-refractive-index optical adhesive with high refractive index, low stress, no polarization interference, and high stability to adapt to the bonding of double-layer grating-type polarizing holographic waveguides of the same material. Summary of the Invention
[0005] To overcome the problems of refractive index mismatch, poor polarization compatibility, high curing stress, and insufficient stability of existing high-refractive-index optical adhesives, this application provides a high-refractive-index optical adhesive, its preparation method, and its application.
[0006] In a first aspect, this application provides a high-refractive-index optical adhesive, employing the following technical solution: A high-refractive-index optical adhesive comprises the following components in parts by weight: 40-60 parts of epoxy acrylate resin with a refractive index ≥1.50, 20-30 parts of sulfur-containing methacrylate monomer, 5-12 parts of silane coupling agent modified inorganic filler, 1.5-3 parts of ultraviolet initiator, 0.5-1.5 parts of polarization stabilizer, 0.2-0.8 parts of leveling agent, and 0.1-0.5 parts of defoamer.
[0007] This application utilizes a multi-component synergistic compounding of epoxy acrylate resin and sulfur-containing methacrylate monomers to obtain a high-refractive-index optical adhesive with low shrinkage stress, no polarization interference, and excellent process adaptability, perfectly matching the bonding requirements of dual-polarizer holographic waveguides. Specifically, this application uses high-refractive-index epoxy acrylate resin and sulfur-containing methacrylate monomers to synergistically construct a high-refractive-index resin matrix, and combines it with silane coupling agents to modify inorganic fillers. Through the complementary gradient of the three components in refractive index, the overall refractive index of the adhesive reaches 1.50-1.55, thereby precisely matching the glass substrate and grating resin layer, fundamentally eliminating interface light scattering and reflection losses. In addition, the high molar refractive index of sulfur atoms in the sulfur-containing monomer molecular chain endows it with polarization-free anisotropic structural characteristics. Combined with polarization stabilizers, it can significantly improve the extinction ratio of the adhesive layer, ensuring that no polarization distortion occurs during polarized light transmission. Secondly, the inorganic filler, after surface grafting modification with a silane coupling agent, can form chemical bonds with the resin matrix, effectively limiting the shrinkage movement of polymer molecular chains during curing and significantly reducing the volume shrinkage rate. The polarization stabilizer also possesses ultraviolet absorption capabilities, effectively inhibiting the photodegradation of azo molecules in the grating and significantly improving the aging resistance and lifespan of the adhesive and bonding components. In summary, the high-refractive-index optical adhesive provided in this application achieves a synergistic improvement in optical matching, polarization adaptation, stress control, process adaptation, and long-term reliability, providing a practical and feasible dedicated adhesive solution for high-quality bonding and encapsulation of polarimetric holographic waveguides.
[0008] Optionally, the polarization stabilizer is selected from one or more of UV-P, Tinuvin 765, light stabilizer 944, and light stabilizer 123.
[0009] Optionally, the leveling agent is selected from one or more of BYK-UV3576, BYK-UV3500, TEGO Rad 2100, KMP-2201, KMP-2410 and KMP321.
[0010] Optionally, the defoamer is selected from one or more of BYK-1794, BYK-1790 and EFKA PB 2770.
[0011] Optionally, the high-refractive-index optical adhesive comprises the following components in parts by weight: 50 parts of epoxy acrylate resin with a refractive index ≥1.50, 25 parts of sulfur-containing methacrylate monomer, 8 parts of silane coupling agent modified inorganic filler, 2 parts of ultraviolet initiator, 1 part of polarization stabilizer, 0.5 parts of leveling agent, and 0.3 parts of defoamer.
[0012] Optionally, the epoxy acrylate resin is a bisphenol F type high-refractive-index epoxy acrylate with a refractive index of 1.58-1.59.
[0013] Optionally, the sulfur-containing methacrylate monomer is selected from one or more of 4,4'-dimercaptodiphenyl sulfide dimethacrylate, 2-phenylthioethyl methacrylate, dithiodiylbis(ethane-2,1-diyl)bis(2-methacrylate), 2-sulfoethyl methacrylate, sulfobetaine methacrylate, and 2-cyano-3,3-di(methylthio)acrylate.
[0014] Optionally, the sulfur-containing methacrylate monomer is a mixture of 4,4'-dimercaptodiphenyl sulfide dimethacrylate and sulfobetaine methacrylate in a weight ratio of 1:(0.1-0.3).
[0015] Optionally, the silane coupling agent modified inorganic filler is KH570 modified zirconium oxide and / or KH570 modified titanium oxide; the particle size of the silane coupling agent modified inorganic filler is 30-80 nm, and the refractive index is 2.1-2.2.
[0016] In this application, the preparation method of the silane coupling agent modified inorganic filler is as follows: First, using anhydrous ethanol, deionized water and glacial acetic acid as solvents, a silane coupling agent is added dropwise at 40-50℃, and hydrolyzed at this temperature for 2 hours to obtain a hydrolysate; then, nano-inorganic filler is added to the hydrolysate, and the mixture is stirred at 40-50℃ and 1000-1500 r / min for 3-5 hours, vacuum dried at 70-80℃ for 10-14 hours, and ground through a 300-mesh sieve to obtain the silane coupling agent modified inorganic filler.
[0017] Optionally, the ultraviolet initiator is a mixture of liquid photoinitiator 184 and photoinitiator 819 in a weight ratio of (2-3):1.
[0018] Secondly, this application provides a method for preparing a high-refractive-index optical adhesive, comprising the following steps: mixing a high-refractive-index epoxy acrylate resin and a sulfur-containing methacrylate monomer evenly; then adding a silane coupling agent to modify an inorganic filler and stirring to disperse evenly; finally adding the remaining components and continuing to stir and mix evenly; and obtaining the high-refractive-index optical adhesive by filtration and vacuum degassing.
[0019] Thirdly, this application provides an application of a high-refractive-index optical adhesive in bonding two polarizing holographic waveguide substrates of the same material.
[0020] In summary, this application has the following beneficial effects: 1. This application utilizes a synergistic compounding of high-refractive-index epoxy acrylate resin, sulfur-containing methacrylate monomer, and silane coupling agent-modified inorganic filler to obtain a high-refractive-index optical adhesive that combines high refractive index, low shrinkage, no polarization interference, and high reliability. Its refractive index can precisely match that of the glass substrate (1.50~1.55) and the grating resin layer (1.50~1.55), fundamentally eliminating interfacial optical loss and polarization distortion. At the same time, it significantly reduces the grating deformation problem caused by bonding stress, and can fully meet the stringent requirements of precision bonding and packaging of dual-piece polarizer holographic waveguides of the same material.
[0021] 2. This application further uses 4,4'-dimercaptodiphenyl sulfide dimethacrylate and sulfobetaine methacrylate in a weight ratio of 1:(0.1-0.3) as sulfur-containing methacrylate monomers, which can give full play to the synergistic effect of the two, thereby improving the extinction ratio, reducing birefringence and shrinkage while maintaining a high refractive index, and obtaining a high-refractive optical adhesive with better extinction ratio and lower birefringence. Detailed Implementation
[0022] This application provides a high-refractive-index optical adhesive comprising the following components in parts by weight: 40-60 parts of epoxy acrylate resin with a refractive index ≥1.50, 20-30 parts of sulfur-containing methacrylate monomer, 5-12 parts of silane coupling agent modified inorganic filler, 1.5-3 parts of ultraviolet initiator, 0.5-1.5 parts of polarization stabilizer, 0.2-0.8 parts of leveling agent, and 0.1-0.5 parts of defoamer.
[0023] This application provides a method for preparing a high-refractive-index optical adhesive, comprising the following steps: mixing a high-refractive-index epoxy acrylate resin and a sulfur-containing methacrylate monomer evenly; then adding a silane coupling agent to modify an inorganic filler and stirring to disperse evenly; finally adding the remaining components and continuing to stir and mix evenly; and obtaining the high-refractive-index optical adhesive by filtration and vacuum degassing.
[0024] This application also provides a method for bonding two identical polarizer holographic waveguide substrates using high-refractive-index optical adhesive, comprising the following steps: (1) Plasma cleaning: Place two glass substrates with polarizer holographic gratings into the cavity of the plasma cleaning equipment, evacuate and then introduce argon gas with a purity of ≥99.999%; set the cleaning power to 80-120W, the distance between the nozzle of the spray gun and the surface of the substrate to 12-15mm, and scan along the surface of the substrate at a uniform speed for 6-10s.
[0025] (2) Ultra-thin coating: Using a 300-mesh micro-grooved roller coating equipment, the high-refractive optical adhesive is uniformly coated on the bonding surface of one of the substrates; the coating speed is 0.6-1.0m / min, the thickness of the adhesive layer after coating and curing is 5-20μm, and the thickness deviation of the adhesive layer is ≤±0.8μm; (3) Low-pressure alignment: The substrate coated with adhesive and another substrate without adhesive are placed on the upper and lower platforms of the high-precision bonding equipment, respectively. The CCD vision alignment system identifies the preset alignment marks on the two substrates to achieve high-precision alignment and bonding. The CCD alignment accuracy is ±1μm. After alignment, the upper platform is lowered to bring the two substrates closer together. The bonding pressure is controlled at 0.02-0.05MPa and the clamping time is 15-20s. Under the above low-pressure conditions, the adhesive spreads naturally and expels interface bubbles by relying on its own fluidity and surface tension.
[0026] (4) Room temperature UV curing: After the bonding and clamping are completed, the bonding area is irradiated and cured using a 365nm wavelength water-cooled LED UV light source; the light intensity of the light source is 700-900mW / cm², and the irradiation curing time is 25-35s; after curing, the bonding components are removed from the bonding equipment and left to stand at room temperature in the dark for 10-15 minutes to complete the bonding.
[0027] In the embodiments of this application, the bisphenol F type high-refractive-index epoxy acrylate is model T-6607 with a refractive index of 1.585; the 4,4'-dimercaptodiphenyl sulfide dimethacrylate is model Sinomer OM386 with a refractive index of 1.65; the zirconium oxide is nanoscale with a particle size of 50 nm and a refractive index of 2.15; the polarization stabilizer is model UV-P; the leveling agent is model BYK-UV3576; and the defoamer is model BYK-1794. All raw materials, reagents, solvents, etc. used in this application are commercially available.
[0028] The following describes this application in further detail with reference to preparation examples, embodiments, and performance testing. Preparation Example 1
[0029] Preparation Example 1 provides a KH570 modified zirconia.
[0030] The preparation method of the above-mentioned KH570 modified zirconia is as follows: Take a 250 mL three-necked reaction flask, add 85 mL of anhydrous ethanol, 12 mL of deionized water, and 3 mL of glacial acetic acid in sequence, stir at room temperature for 5 min to mix, and heat to 45℃ in a water bath; weigh 2.5 g of silane coupling agent KH570, and slowly add it dropwise to the above-mentioned alcohol-acid mixed solvent, stirring at 300 r / min throughout the process. After the addition is complete, keep it sealed at 45℃ for 2 h for hydrolysis to obtain silane hydrolysate; add 10 g of high-purity nano-zirconia powder with a particle size of 50 nm and a refractive index of 2.15 to the hydrolysate, adjust the stirring speed to 1200 r / min, and stir at 45℃ for 4 h, supplementing with 300 g of acetic acid every 1 h. W was ultrasonically dispersed for 10 min; after the reaction was completed, it was cooled to room temperature and vacuum filtered. The filter cake was washed three times with anhydrous ethanol. The washed filter cake was placed in a vacuum drying oven and dried for 12 h at 75℃ and a vacuum degree ≤-0.09MPa. The dried powder was taken out, ground and pulverized by agate grinding, and passed through a 300-mesh sieve to obtain KH570 modified zirconia. Examples 1-3
[0031] Examples 1-3 each provide a high-refractive-index optical adhesive.
[0032] The difference in the above embodiments lies in the amount of epoxy acrylate resin, sulfur-containing methacrylate monomer, and KH570 modified zirconium oxide added, as shown in Table 1 below.
[0033] The preparation method of the high-refractive-index optical adhesive provided in Examples 1-3 includes the following steps: mixing high-refractive-index epoxy acrylate resin and sulfur-containing methacrylate monomer (4,4'-dimercaptodiphenyl sulfide dimethacrylate methyl methacrylate) evenly; then adding KH570 modified zirconium oxide and stirring to disperse evenly; finally adding 2g of UV initiator (liquid photoinitiator 184 and photoinitiator 819 in a weight ratio of 2.5:1), 1g of polarization stabilizer UV-P, 0.5g of leveling agent BYK-UV3576, and 0.3g of defoamer BYK-1794, and continuing to stir and mix evenly; after filtration and vacuum degassing, the high-refractive-index optical adhesive is obtained.
[0034] Table 1. Amounts of some raw materials used in the high-refractive optical adhesives provided in Examples 1-3 and Comparative Examples 1-4 Examples 4-10
[0035] Examples 4-10 each provide a high-refractive-index optical adhesive.
[0036] The difference between the above embodiments and Embodiment 2 lies in the type and ratio of sulfur-containing methacrylate monomers, as shown in Table 2 below.
[0037] Table 2. Types and proportions of sulfur-containing methacrylate monomers in Examples 2 and 4-10 Comparative Examples 1-4
[0038] Comparative Examples 1-4 each provide a high-refractive-index optical adhesive.
[0039] The difference between the above comparative example and Example 2 is that the amount and type of some raw materials are as shown in Table 1. Application Example 1-10
[0040] Application Examples 1-10 respectively use the high-refractive-index optical adhesive provided in Examples 1-10 to bond two polarizer holographic waveguide substrates of the same material. The specific steps are as follows: (1) Plasma cleaning: Place two glass substrates with polarizer holographic gratings into the cavity of the plasma cleaning equipment, evacuate and then introduce argon gas with a purity of ≥99.999%; set the cleaning power to 100W, the distance between the nozzle of the spray gun and the surface of the substrate to 12mm, and scan along the surface of the substrate at a uniform speed for 10s.
[0041] (2) Ultra-thin coating: A 300-mesh micro-grooved roller coating equipment is used to uniformly coat the high-refractive optical adhesive onto the bonding surface of one of the substrates; the coating speed is 0.8m / min, the thickness of the adhesive layer after coating and curing is 10μm, and the thickness deviation of the adhesive layer is ≤±0.8μm; (3) Low-pressure alignment: The substrate coated with adhesive and another substrate without adhesive are placed on the upper and lower platforms of the high-precision bonding equipment, respectively. The CCD vision alignment system identifies the preset alignment marks on the two substrates to achieve high-precision alignment and bonding. The CCD alignment accuracy is ±1μm. After alignment, the upper platform is lowered to bring the two substrates closer together. The bonding pressure is controlled at 0.04MPa and the clamping time is 20s. Under the above low-pressure conditions, the adhesive spreads naturally and expels interface bubbles by relying on its own fluidity and surface tension.
[0042] (4) Room temperature UV curing: After the bonding and clamping are completed, the bonding area is irradiated and cured using a water-cooled LED UV light source with a wavelength of 365nm; the light intensity of the light source is 800mW / cm², and the curing time is 30s; after curing, the bonding components are removed from the bonding equipment and left to stand for 15min under room temperature and light-proof conditions to complete the bonding. Compare and contrast examples 1-4
[0043] In comparative application examples 1-4, the high-refractive-index optical adhesive provided in comparative examples 1-4 was used to bond two polarizer holographic waveguide substrates of the same material. The bonding method was the same as in example 2. Performance testing
[0044] Performance tests were performed on Examples 1-10, Comparative Examples 1-4, Application Examples 1-10, and Comparative Application Examples 1-4, and the results are shown in Table 3 below.
[0045] (1) Refractive index: The adhesive was applied to the clean release PET film using a coater. The thickness of the adhesive film after curing was controlled to be 50 μm. After complete curing under 365 nm ultraviolet light, the film was completely peeled off to obtain a defect-free independent adhesive film. The refractive index of the adhesive film was measured using an Abbe refractometer at 25 °C and 589 nm (D sodium light) wavelength.
[0046] (2) Curing shrinkage rate: The liquid density of the adhesive at 25℃ was determined using the hydrometer bottle method; the adhesive was filled into a polytetrafluoroethylene mold and irradiated with a 365nm, 800 mW / cm² ultraviolet light source for 30s to completely cure it into a solid block. The solid density of the cured block was determined by the water displacement method; the volume shrinkage rate was calculated based on the density before and after curing. The calculation formula is: S V =(1−ρ l / ρ s ×100%, where S V ρ is the volume shrinkage rate. l ρ is the density of the liquid glue. s This represents the density of the cured adhesive block.
[0047] (3) Polarization interference: Apply glue to a quartz substrate (quartz itself has no polarization interference), peel it off after curing or test it directly, and use a polarization spectrometer and polarization interferometer to measure the extinction ratio and birefringence of polarized light after passing through the glue film.
[0048] (4) UV aging resistance: The adhesive is applied to the quartz substrate, cured and placed in the QUV UV aging chamber for 500h accelerated aging. The yellowing index Δb before and after aging is measured with a colorimeter.
[0049] (5) Temperature cycle reliability: The waveguide substrates bonded in the application example and the comparative application example are placed in a high and low temperature humidity chamber and cyclically tested between -40℃ and 85℃ (heating / cooling rate is 5℃ / min, and each temperature point is kept at 30min). After 500 cycles, the substrates are taken out and the interface is observed to see if there are phenomena such as delamination, whitening, or peeling.
[0050] Table 3 Performance test results of high-refractive-index optical adhesive and polarizer holographic waveguide substrate
[0051] As shown in Table 3, the high-refractive optical adhesives of Examples 1-10 have a refractive index of 1.50-1.55, a volume shrinkage rate of 0.7-1.1%, an extinction ratio of 1100:1-1900:1, and a birefringence Δn of 1.8 × 10⁻⁶. -5 ~5.7×10 -5The 500-hour UV yellowing index Δb is 0.5-0.9, and the temperature resistance cycle has passed 500 cycles without delamination, whitening, or peeling. This indicates that the high-refractive-index optical adhesive provided in this application possesses comprehensive properties including high refractive index, low curing shrinkage, no polarization interference, high light transmittance, and aging resistance. It can precisely match the optical parameters of the glass substrate and the grating layer, making it suitable for the precision bonding and encapsulation of dual-layer polarizer holographic waveguides of the same material.
[0052] The test results of Examples 1-3 and Comparative Examples 1-3 show that the refractive index of Examples 1-3 is 1.50-1.53, the volume shrinkage rate is 0.8-1.1%, the extinction ratio is 1200:1-1600:1, and the birefringence Δn is 3.4×10⁻⁶. -5 ~5.7×10 -5 The 500-hour UV yellowing index Δb was 0.6-0.9, and the temperature resistance passed 500 cycles without delamination, whitening, or peeling. In contrast, in Comparative Example 1, the excessive resin (70 parts) and insufficient sulfur-containing monomer (10 parts) resulted in insufficient crosslinking density, leading to an optical adhesive with a refractive index of only 1.48, a volume shrinkage rate as high as 2.5%, an extinction ratio of only 800:1, and a 500-hour UV yellowing index Δb as high as 1.8. It also showed interface whitening after only about 300 temperature cycles. In Comparative Example 2, the excessive monomer (40 parts), insufficient resin (30 parts), and excessive filler (15 parts) resulted in an optical adhesive with a volume shrinkage rate as high as 3.2%, a 500-hour UV yellowing index Δb as high as 2.1, and delamination after about 250 temperature cycles. Comparative Example 3 used unmodified zirconia instead of KH570 modified zirconia. Although the refractive index remained at 1.50, the volume shrinkage rate was as high as 2.8%, the extinction ratio was only 600:1, and the birefringence Δn was as high as 1.2 × 10⁻⁶. -4 The UV yellowing index Δb reached as high as 2.5 after 500 hours, and interface whitening and delamination occurred after about 150 temperature cycles. Therefore, unmodified inorganic fillers cannot form chemical bonds with the resin matrix and cannot effectively suppress curing shrinkage and disperse stress. This application uses high-refractive-index epoxy acrylate resin, sulfur-containing methacrylate monomer, and silane coupling agent modified inorganic fillers as raw materials, and adjusts their dosage to a specific range to achieve synergistic optimization of high refractive index, low shrinkage rate, and excellent reliability.
[0053] The test results of Examples 2 and 4-10 show that, in Examples 2 and 4-5, methyl 4,4'-dimercaptodiphenyl sulfide dimethacrylate, methyl 2-cyano-3,3-di(methylthio)acrylate, or sulfobetaine methacrylate were used as sulfur-containing methacrylate monomers. The resulting high-refractive optical adhesives had a refractive index of 1.50-1.52, an extinction ratio of 1100:1-1500:1, and a birefringence Δn of 4.1 × 10⁻⁶. -5 ~5.6×10 -5Examples 6 and 10 use methyl 4,4'-dimercaptodiphenyl sulfide dimethacrylate and methyl 2-cyano-3,3-di(methylthio)acrylate in a weight ratio of 1:0.2, or methyl 4,4'-dimercaptodiphenyl sulfide dimethacrylate and sulfobetaine methacrylate in a weight ratio of 1:1, as sulfur-containing methacrylate monomers. The resulting high-refractive optical adhesives have a refractive index of 1.52-1.53, an extinction ratio of 1400:1-1500:1, and a birefringence Δn of 4.4 × 10⁻⁶. -5 ~5.3×10 -5 Examples 7-9 used 4,4'-dimercaptodiphenyl sulfide dimethacrylate and sulfobetaine methacrylate in a weight ratio of 1:(0.1-0.3) as sulfur-containing methacrylate monomers. The resulting high-refractive optical adhesives had a refractive index of 1.54-1.55 (≥1.54), an extinction ratio of 1800:1-1900:1 (≥1800:1), and a birefringence Δn of 1.8 × 10⁻⁶. -5 ~2.3×10 -5 (≤2.5×10) -5 Therefore, it is evident that this application uses 4,4'-dimercaptodiphenyl sulfide dimethacrylate and sulfobetaine methacrylate in a weight ratio of 1:(0.1-0.3) as sulfur-containing methacrylate monomers, which can fully leverage the synergistic effect of the two, thereby further improving the extinction ratio, reducing birefringence and shrinkage while maintaining a high refractive index, and obtaining a high-refractive optical adhesive with a better extinction ratio and lower birefringence.
[0054] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A high-refractive-index optical adhesive, characterized in that, The product comprises the following components in parts by weight: 40-60 parts of epoxy acrylate resin with a refractive index ≥1.50, 20-30 parts of sulfur-containing methacrylate monomer, 5-12 parts of silane coupling agent modified inorganic filler, 1.5-3 parts of UV initiator, 0.5-1.5 parts of polarization stabilizer, 0.2-0.8 parts of leveling agent, and 0.1-0.5 parts of defoamer.
2. The high-refractive optical adhesive according to claim 1, characterized in that, The high-refractive-index optical adhesive comprises the following components in parts by weight: 50 parts of epoxy acrylate resin with a refractive index ≥1.50, 25 parts of sulfur-containing methacrylate monomer, 8 parts of silane coupling agent modified inorganic filler, 2 parts of ultraviolet initiator, 1 part of polarization stabilizer, 0.5 parts of leveling agent, and 0.3 parts of defoamer.
3. The high-refractive optical adhesive according to claim 1, characterized in that, The epoxy acrylate resin is a bisphenol F type high-refractive-index epoxy acrylate with a refractive index of 1.58-1.
59.
4. The high-refractive optical adhesive according to claim 1, characterized in that, The sulfur-containing methacrylate monomer is selected from one or more of 4,4'-dimercaptodiphenyl sulfide dimethacrylate, 2-phenylthioethyl methacrylate, dithiodiylbis(ethane-2,1-diyl)bis(2-methacrylate), 2-sulfoethyl methacrylate, sulfobetaine methacrylate, and 2-cyano-3,3-di(methylthio)acrylate.
5. The high-refractive optical adhesive according to claim 1, characterized in that, The sulfur-containing methacrylate monomer is a mixture of 4,4'-dimercaptodiphenyl sulfide dimethacrylate and sulfobetaine methacrylate in a weight ratio of 1:(0.1-0.3).
6. The high-refractive optical adhesive according to claim 1, characterized in that, The silane coupling agent modified inorganic filler is KH570 modified zirconium oxide and / or KH570 modified titanium oxide; the particle size of the silane coupling agent modified inorganic filler is 30-80 nm, and the refractive index is 2.1-2.
2.
7. The high-refractive optical adhesive according to claim 1, characterized in that, The ultraviolet initiator is a mixture of liquid photoinitiator 184 and photoinitiator 819 in a weight ratio of (2-3):
1.
8. The method for preparing the high-refractive optical adhesive according to any one of claims 1-7, characterized in that, Includes the following steps: High-refractive-index epoxy acrylate resin and sulfur-containing methacrylate monomer are mixed evenly; then, silane coupling agent is added to modify inorganic filler, and the mixture is stirred and dispersed evenly; finally, the remaining components are added, and the mixture is stirred and mixed evenly; after filtration and vacuum degassing, high-refractive-index optical adhesive is obtained.
9. The application of the high-refractive-index optical adhesive as described in any one of claims 1-7 in bonding two identical polarizer holographic waveguide substrates.